Adeno-associated virus for cystic fibrosis gene therapy - Martini,S.V. (2011)
Gene therapy is an alternative treatment for genetic lung disease, especially monogenic disorders such as cystic fibrosis. Cystic fibrosis is a severe autosomal recessive disease affecting one in 2500 live births in the white population, caused by mutation of the cystic fibrosis transmembrane conductance regulator (CFTR). The disease is classically characterized by pancreatic enzyme insufficiency, an increased concentration of chloride in sweat, and varying severity of chronic obstructive lung disease. Currently, the greatest challenge for gene therapy is finding an ideal vector to deliver the transgene (CFTR) to the affected organ (lung). Adeno-associated virus is the most promising viral vector system for the treatment of respiratory disease because it has natural tropism for airway epithelial cells and does not cause any human disease. This review focuses on the basic properties of adeno-associated virus and its use as a vector for cystic fibrosis gene therapy.